2022
DOI: 10.3389/fimmu.2022.947242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cellular aging on memory T-cell homeostasis

Abstract: The fact that T-cell numbers remain relatively stable throughout life, and that T-cell proliferation rates increase during lymphopenia, has led to the consensus that T-cell numbers are regulated in a density-dependent manner. Competition for resources among memory T cells has been proposed to underlie this ‘homeostatic’ regulation. We first review how two classic models of resource competition affect the T-cell receptor (TCR) diversity of the memory T-cell pool. First, ‘global’ competition for cytokines leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…This dynamic will lead to the accumulation of older memory CD4 T cells. In contrast, a recent study argued that an increase in cell mortality with cell age may act to preserve the TCR diversity of memory populations as an individual ages, and hence be beneficial [38]. In the latter study, cell aging was directly associated with cell divisions, whereas here we defined age to be a heritable clock that measures the time since a cell’s ancestor entered the memory pool.…”
Section: Discussionmentioning
confidence: 95%
“…This dynamic will lead to the accumulation of older memory CD4 T cells. In contrast, a recent study argued that an increase in cell mortality with cell age may act to preserve the TCR diversity of memory populations as an individual ages, and hence be beneficial [38]. In the latter study, cell aging was directly associated with cell divisions, whereas here we defined age to be a heritable clock that measures the time since a cell’s ancestor entered the memory pool.…”
Section: Discussionmentioning
confidence: 95%
“…Based on in silico simulations, in which memory T cells compete for survival or proliferation factors, we have recently shown that the diversity of the memory T‐cell repertoire tends to reach higher levels if memory T cells are relatively short‐lived. A relatively rapid turnover of memory T cells creates more flexibility to store new memories, and hence makes the immune system more agile 113 …”
Section: Discussionmentioning
confidence: 99%
“…A relatively rapid turnover of memory T cells creates more flexibility to store new memories, and hence makes the immune system more agile. 113 The observed differences between clean laboratory mice and mice exposed to wild microbiota raise the question how memory T-cell dynamics may differ between humans living in environments with different levels of exposure to pathogens. Weisman et al 114 recently demonstrated the drastic effects that helminth infections can have on the T-cell pool.…”
Section: Con Clus I On S and Future Direc Tionsmentioning
confidence: 99%
“…Aging in animals and especially in humans is the natural result of entropy in cells as part of tissues and organs of the human body. It is a slow, inexorable process that leads to a continuous increase in molecular errors in DNA and proteins, increasingly disrupting the homeostasis of cells, tissues, and organs 3 , 4 . Accordingly, a set of tools has been established to analyze aging on a cellular level.…”
Section: Introductionmentioning
confidence: 99%